Law No. 13 of the year 2022 Amending Certain Provisions of the Capital Market Law Promulgated by Law No. 95 of the Year 1992 = قانون رقم 13 لسنة 2022 بتعديل بعض أحكام قانون سوق رأس المال الصادر بالقانون رقم 95 لسنة 1992 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic